Reseña de Cuarteto Otal, J. (2003). Cosas que se hacen.Esquemas sintácticos-semánticos agentivos del español. - Devís Márquez, Pedro Pablo (Pragmalingüística, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Se trata de una reseña sobre Cuarteto Otal, J. (2003). Cosas que se hacen. Esquemas sintácticos-semánticos agentivos del español.